Time perception’s effect on individual differences and behavior: the mediating role of impulsivity on the relationship between time perception and intertemporal health behaviors - Daugherty, James R. (Kansas State University, 2011)
This research tested a general mediation model which proposes that individual differences (e.g., impulsivity, delay discounting, and time orientation) mediate the relationship between time perception (one’s subjective experience of the passage of time relative to actual time) and intertemporal behavior (decision-making involving tradeoffs between costs and rewards in both the present and the future). Study I did not find evidence to support the general mediation model and found that time perception was only weakly correlated with individual differences and intertemporal behavior (average r = .06) . Study II found tentative support for the proposed mediation model: individual differences in impulsivity fully mediated the relationship between time perception and intertemporal behavior in 4 separate mediation models. Three additional mediation models met the assumptions of mediation, demonstrating indirect effects significantly different from zero, but did not fully mediate the relationship between time perception and intertemporal behavior. In general, the mediation models explored in Study II (both fully and partially mediated) suggest that self-report impulsivity mediates the relationship between time perception and intertemporal health behaviors, like hours of sleep slept per night, sociosexual orientation, and frequency of eating breakfast. The findings from Study II suggest that how time is perceived influences intertemporal behavior indirectly by influencing impulsivity. Guidelines to aid future research linking time perception to individual differences and intertemporal behavior are provided.
Keywords: time perception; impulsivity; delay discounting; time perspective; environmentism; health behaviors; Psychology (0621)